Andi Depu and Women’s Leadership in the Colonial Era: A Study of Feminism - Miftahul Jannah (LPPM IAIN Parepare, 2022)
This research departs from the problem of the existence of stereotypes against women who have intellectual qualities below men, because emotional feelings dominate in women. This has implications for the view that women are unfit to lead and ideal women are those who work in the kitchen, but such stereotypes actually lead to various discriminations against women. In this article, we will present the figure of Andi Depu as a female leader in Balanipa, who fought against the invaders. The methodology used in this study, namely the type of research: Library Research or literature study, nature of the research: qualitative, research method: descriptive analysis and using a feminist approach. The results in this study, namely: Andi Depu's leadership is a form of anti-thesis to the perception of society that views women as weak creatures, so they cannot be used as leaders. In addition, Andi Depu's leadership is also a form of anti-thesis to the misogynistic view which states that women only play a role in the domestic sphere and do not have a social role.